Strategic Steps Of The Human Rights Commissioner In Handling Cases Of Human Rights Violations - Dewi Iriani; Muhammad Fauzan; Rohmah Maulidia (Universitas Muhammadiyah Surakarta, 2022)
The Republic of Indonesia’s reformation era, many human rights violations occurred during, including human rights violations in cases of Trisakti, Semanggi 1, and Semanggi 2. There were ethnic, racial, and religious conflicts. The state is obliged to provide protection for victims of human rights violations. The Human Rights Commissioner plays a role in issuing policies/decisions to resolve cases of human rights violations that require a long time to resolve. Unfortunately, the term of office of the Chairperson/Deputy of the National Commission for Human Rights (NCHR) only lasts 2 years and 6 months after which they can be re-elected. This is regulated in Regulation of the NCHR No. 2 of 2019 concerning the Order of the NCHR. It is impossible to properly settle cases of human rights violations with a commissioner term of office that is only limited to 2 years and 6 months. Therefore, legal construction is required to revise the term of office of the NCHR Chairperson and Deputy. This paper was library research, namely research using library data from books and journals. It was found that the NCHR had trouble resolving human rights cases due to political pressures. Then, the NCHR Chairperson and Deputy’s term of office should be revised to five years so that they have more time to serve the people by resolving cases of human right violations.